The Effectiveness of Restorative Justice Implementation in the Settlement of Juvenile Criminal Cases in the Jurisdiction of Mataram City - Prima, Agus; Hidayat, Wahyu; Muis, Abdullah (Justicia Insight, 2025)
The handling of juvenile criminal cases requires a different approach from conventional criminal justice systems, considering that children are individuals still undergoing development. The application of restorative justice offers an alternative means of resolving juvenile criminal cases by prioritizing the restoration of social relationships, accountability of the offender, and protection of children's rights. This study aims to analyze the effectiveness of restorative justice implementation in resolving juvenile criminal acts within the jurisdiction of Mataram City, by examining the process, challenges, and its impact on offenders, victims, and the community. This research employs an empirical juridical approach, utilizing data collection methods such as interviews, document analysis, and observations of several cases resolved through restorative justice mechanisms. The findings indicate that the implementation of restorative justice in Mataram City is relatively effective in diverting children from lengthy legal proceedings and promoting more humane and just resolutions. However, its effectiveness is still influenced by factors such as law enforcement officers’ understanding, community involvement, and the availability of supporting facilities. Therefore, it is necessary to enhance institutional capacity and inter-agency synergy to support the optimal implementation of restorative justice.